Exploring perceptions of the impacts of resource development: A Q-methodology study. Issue 3 (August 2015) - Chapman, Rachel; Tonts, Matthew; Plummer, Paul
Abstract: A mining boom starting in the mid 2000s has transformed the economic and social structure of many of Western Australia's remote resource-dependant towns. To date, research on these changes have tended to either involve broad cross-sectional analyses across multiple localities, or have involved narrow single town case studies focused on quite specific issues, such as housing, service provision and employment. Yet local experiences and perceptions of rapid resource-led development are likely to be diverse and multifaceted. This study uses Q-methodology to explore local residents experiences and perceptions of change in two resource-dependent towns in Western Australia's Pilbara region. It identifies quite distinctive sets of experiences both within and between each community. The findings suggest that the implications of resource development are highly nuanced, and dependent not only on individual experiences, but also local histories, cultures and values.